A SYNTACTIC ANALYSIS OF ENGLISH NEWS ARTICLES IN THE JAKARTA POST AND ITS IMPLICATIONS FOR ENGLISH LANGUAGE TEACHING IN INDONESIA - Zuindra; HIdayati; Misla Geubrina; Vinya Hafizah Arini; Siti Aisyah (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2025)
The increasing use of authentic English materials in Indonesian English as a Foreign Language (EFL) classrooms has highlighted the need to understand the syntactic characteristics of newspaper discourse. However, limited studies have comprehensively examined the syntactic features of English news articles and their implications for English language teaching in Indonesia. This study aimed to analyze the syntactic features employed in The Jakarta Post news articles and explore their pedagogical implications for English language teaching. A qualitative descriptive design was adopted using document analysis. The data consisted of twenty news articles selected through purposive sampling from The Jakarta Post. The collected data were analyzed through data condensation, data display, and conclusion drawing following the interactive model proposed by Miles, Huberman, and Saldaña. The findings revealed that all four major sentence types—simple, compound, complex, and compound-complex—were identified, with complex sentences occurring most frequently. The analysis also indicated the extensive use of coordination and subordination to organize information effectively in authentic journalistic discourse. These findings suggest that The Jakarta Post provides authentic linguistic input that can support the teaching of English syntax, reading comprehension, and academic writing. Consequently, authentic newspaper texts can serve as valuable instructional resources for enhancing students' syntactic awareness and bridging the gap between grammatical knowledge and real-world language use